Rwanda: Cost effective options for inclusive and sustainable development - Aragie, Emerta A.; Niyonsingiza, Josue; Thurlow, James; Warner, James; Xu, Valencia Wenqian (International Food Policy Research Institute, 2025)
In this policy brief, we present research findings of a systematic evaluation and ranking of investment options for Rwanda’s agrifood system based on their cost-effectiveness in achieving multiple devel opment outcomes, including agrifood gross domestic product (GDP) growth, agrifood job creation, poverty reduction, declining rates of undernourishment, and lowering diet deprivation. Additionally, the study assesses their environmental footprint, focusing on water consumption, land use, and emissions. Investments in small and medium enterprise (SME) processors are shown to be the most cost-effective at expanding agrifood GDP and employment, while extension and advisory services on livestock and climate emerge as the most efficient farmer-facing investments. However, crop ex tension services rank least in cost-effectiveness for economic and social outcomes. However, many cost-effective investments have relatively high environmental footprints, which highlights potential tradeoffs. The study further reveals shifts in the cost-effectiveness ranking of investment options overtime and when extreme production shocks occur.